M1 M2 macrophage expression in menstrual blood flakes of women with endometriosis - Yulisa Haslinda; Ashon Sa’adi; Hendy Hendarto; Faroek Hoesin (Majalah Obstetri dan Ginekologi, 2016)
Objectives: to measure and prove the increase of panmacrophage, macrophages M1 and M2 expression and decrease of ratio of M1/M2 in menstrual blood flakes of women with endometriosis. Materials and Methods: This study was a cross sectional observational analytic study conducted on 30 subjects with endometriosis and non-endometriosis. Immunohistochemical staining was done on a sample of menstrual blood flakes of subjects study who were taken at the second or third day of menstrual cycles with CD68 and CD163 antibody to measure the expression of panmacrophage and M2 macrophages. Expression of M1 macrophages is the approach of a reduction expression of panmacrophage with M2 macrophages.Results: Expression of  M1, M2 and the ratio M1/M2 in the both of groups had a normal distribution then continued by independent t-test with one-tailed α (0.05). Probability was considered statistically significant at p <0.05 with a confidence interval of 95%. Based on the statistical result, Mφ macrophage expression in endometriosis and control group amounted to 3.62 ± 0.50 and 2.80 ± 0.64 (p =0.0005) with non parametric test. The expression of M1 macrophages in endometriosis group and non endometriosis were respectively 1.40 ± 0.35 and 1.33 ± 0.40 (p =0.3005) and the expression of M2  in both of group, respectively of 2.23 ± 0.41 and 1.47 ± 0.36 (p =0.0005). The ratio of M1/M2, the endometriosis group and non endometriosis, respectively of 0.65 ± 0.20 and 0.92 ± 0.24 (p =0.0015).Conclusion: this study were significant increased in the panmacrophage Mφ, M2 macrophages expression on a woman's menstrual blood flakes endometriosis and significant decreased in ratio M1/M2 in the woman's menstrual blood flakes endometriosis.